Late Cenozoic geology, Ancient Pacific Margin Natmap Project, report 4: paleomagnetic and geomorphic evidence for Brunhes-age volcanism, Fort Selkirk and Rosebud Creek area, Yukon Territory - Huscroft, Crystal A.; Barendregt, René W.; Jackson, Lionel E. (Geological Survey of Canada, 2001)
Open access Normally magnetized, valley-filling basalt flows extend more than 10 km down the Yukon River valley from the Fort Selkirk area. These flows are locally overlain by gravel and terminate at the level of the contemporary Yukon River flood plain, suggesting a middle to late Pleistocene age for this previously unrecognized eruptive event. Unlike other valley-filling phases of the Selkirk Volcanic Group, this eruption postdates the Pliocene to early Pleistocene pre-Reid glaciations. Normal magnetism was also determined for basalt flows underlying terraces in the area of the Rosebud Creek-Grand Valley Creek confluence, 60 km to the northwest of the Fort Selkirk area. Based on their unique geomorphic and stratigraphic settings, the Rosebud basalt flows may represent yet another period of Pleistocene volcanism which predates one of the pre-Reid glaciations in the central Yukon Territory. Yes